Perspectivas de valorização e conservação do patrimônio geo-mineiro da localidade de Minas do Camaquã (Caçapava do Sul, RS) - Domingues, Silvio Avila (2016)
Mining in operation phase allows very much. Minas do Camaquã is a district within the municipality of Caçapava do Sul who lived a moment of great flow, time when mining was carried out in the locality. It is a place that draws attention for its landscape importance and this provides the attraction of visitors, many of these, practitioners of adventure sports. Given this panorama this dissertation aims a management plan to the location where they can be integrated valuation practices and conservation of exposed geomineiro heritage in the locality, its geotouristic use, which present themselves abandoned mining structures and also their relationship with adventure sports. It was possible to set for this representative local plan in Vila Minas do Camaquã in terms of evolution of the site, with examples based on national and international management models that fit in areas that have environmental liabilities of mining and can be reused. The local community contribution as the future perspective, taking into account their opinion for structuring content and sites for the implementation of educational interpretive panels containing information on the geological formation and history of the town during the mining period. The methodological procedures of this qualitative research were based on fieldwork which were community stakeholders interviewed that were thought the management plan strategies and the definition of geological points, geomorphological and historical relevant interest in community building interpretive content of this existing geomining heritage in the locality and the construction of a geotouristic map so that the most relevant points of the locality can be visited. For the results are recommendations for a management plan where the town can be considered a tourist attraction, and it can be treated as a distinct territorial unit similar to a "mining park" or a "territory museum", is the hope of local resident in a brief return of mining beyond its nostalgia regarding the time when mining work. There is the prospect for future community situation is better, they have assistance from the government as part of infrastructure and urban facilities, in addition to health care.